Toward understanding short‐term personal information preservation: A study of backup strategies of end users. (15th June 2015) - Kljun, Matjaž; Mariani, John; Dix, Alan
Abstract : The segment of companies providing storage services and hardware for end users and small businesses has been growing in the past few years. Cloud storage, personal network‐attached storage (NAS), and external hard drives are more affordable than ever before and one would think that backing up personal digital information is a straightforward process nowadays. Despite this, small group studies and corporate surveys show the opposite. In this paper we present the results from a quantitative and qualitative survey of 319 participants about how they back up their personal computers and restore personal information in case of computer failures. The results show that the majority of users do manual, selective, and noncontinuous backups, rely on a set of planned and unplanned backups (as a consequence of other activities), have inadequate knowledge about possible solutions and implications of using known solutions, and so on. The study also reveals that around a fifth of all computers are not backed up, and a quarter of most important files and a third of most important folders at the time of the survey could not be (fully) restored in the event of computer failure. Based on the results, several implications for practice and research are presented.